Analisis Pengaruh Variasi Kecepatan Putaran Dan Jarak Celah Mata Pisau Pada Mesin Pengupas Biji Kopi Terhadap Hasil Pengupasan - Muhammad Prayogo; Diah Wulandari (CV. SINAR HOWUHOWU, 2026)
This study aims to investigate the effect of machine rotational speed and blade clearance on the performance of a wet coffee cherry hulling machine. The performance parameters evaluated include the percentage of peeled coffee cherries, the percentage of unpeeled cherries, and machine capacity. Identifying the influence of these parameters is expected to determine the optimal operating conditions that enable an effective and efficient peeling process without causing damage to the coffee beans. A common problem encountered in the field is the suboptimal peeling of wet coffee cherries, indicated by a high proportion of unpeeled cherries or bean damage due to improper machine settings. In practice, farmers and coffee processors often rely on approximate adjustments of blade clearance and rotational speed, resulting in inconsistent peeling quality and limited machine capacity. An experimental method was employed by testing a wet coffee cherry hulling machine at rotational speeds of 300 rpm, 350 rpm, and 420 rpm, combined with blade clearances of 2 mm, 4 mm, and 6 mm. The results show that smaller blade clearances produce higher peeling percentages, while increasing rotational speed tends to improve machine capacity. The optimal operating condition was achieved at a rotational speed of 420 rpm with a blade clearance of 2 mm, yielding the highest peeling percentage and the greatest machine capacity.